A 1D-FDM Transmission Line Model for Partial Discharge Current Simulations Validated Against Needle-Plate HVDC Laboratory Experiments: Calculations of Ionized Air Conductivity - Rodrigo M. S. de Oliveira; Nathan M. Lopes; Júlio A. S. do Nascimento (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract In this paper, we present a novel numerical model for simulating partial discharges (PDs) transient currents excited by high-voltage DC (HVDC) systems. The model is based on the telegraph equations, which are solved in the time domain via the finite-difference method (FDM). With the proposed model, one can simulate air ionization through its distinct phases based on the electric field’s magnitude. This study specifically provides effective electrical conductivity of ionized air over time and space, calculated in the discharge channel also as a function of voltage and gap distance in a needle-plate setup. Validation is performed against experimental results from our laboratory experiments, demonstrating agreement despite the model’s one-dimensional nature. The simplicity of the model leads to much smaller simulation times (up to two minutes) compared to more complex three-dimensional models (typically requiring hours to complete), highlighting its potential for efficient PD analysis and future developments of general PD models based on effective plasma conductivity.